2013
DOI: 10.1111/jdi.12111
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of safety and efficacy of insulin‐to‐liraglutide switch in Japanese type 2 diabetes: A caution against inappropriate use in patients with reduced β‐cell function

Abstract: Aims/IntroductionThe safety and efficacy of insulin‐to‐liraglutide switch in type 2 diabetes has not been studied adequately. Here, we retrospectively characterize clinical parameters that might predict insulin‐to‐liraglutide treatment switch without termination due to hyperglycemia, and examine the effects of switching the therapies on glycated hemoglobin (HbA1c) and bodyweight in Japanese type 2 diabetes.Materials and MethodsJapanese type 2 diabetes patients who underwent the switch of therapy were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Ross also noted that the benefits of GLP-1 RA were more prominent in patients with shorter duration T2DM in one report on liraglutide. This is consistent with several reports demonstrating that the HbA1c-lowering effects of liraglutide depend on residual b-cell function such as may be found in patients with shorter duration of the disease [15][16][17] . Despite the possible amelioration of diabetic complications independently of glycemic control, there are important issues to be considered, including patient health-related quality of life (HRQOL) and cost-effectiveness; GLP-1 RAs involve injections, which often lower HRQOL, and there are considerably higher medical costs in comparison with oral anti-diabetic drugs.…”
supporting
confidence: 91%
“…Ross also noted that the benefits of GLP-1 RA were more prominent in patients with shorter duration T2DM in one report on liraglutide. This is consistent with several reports demonstrating that the HbA1c-lowering effects of liraglutide depend on residual b-cell function such as may be found in patients with shorter duration of the disease [15][16][17] . Despite the possible amelioration of diabetic complications independently of glycemic control, there are important issues to be considered, including patient health-related quality of life (HRQOL) and cost-effectiveness; GLP-1 RAs involve injections, which often lower HRQOL, and there are considerably higher medical costs in comparison with oral anti-diabetic drugs.…”
supporting
confidence: 91%
“…Consistent with this view, studies have shown that higher C-peptide secretion is predictive of a larger treatment response to liraglutide, 12,14 or a greater likelihood of success when switching patients to liraglutide from insulin. 15,16 The mean reduction in HbA1c with liraglutide was smaller for patients treated with insulin, relative to patients receiving other therapies, but nevertheless remained clinically significant. Recent clinical studies have shown that combinations of GLP-1 agonists and insulin are a rational treatment choice, as the inclusion of the GLP-1 agonist improves antihyperglycaemic efficacy while limiting the weight gain and hypoglycaemia associated with insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the liraglutide treatment may have effectively compensated for a GLP-1 deficiency. Although the patient's GLP-1 concentration was not measured, his capacity for insulin secretion and insulin sensitivity robustly improved following the administration of liraglutide therapy; the patient exhibited a lower level of CPR secretion and a much lower CPI than the estimated predictive values for better glycemic control after the insulin-to-liraglutide switch (11,12), and the serum CPR and CPI values subsequently markedly improved. Although preservation of the beta cell function is usually required for effective treatment with liraglutide, there may well be certain highly responsive patients, similar to the present patient, with a short duration of diabetes and a low CPI.…”
Section: Discussionmentioning
confidence: 94%